2020
DOI: 10.1016/j.jbusres.2019.09.020
|View full text |Cite
|
Sign up to set email alerts
|

The effect of entrepreneurial orientation on firm performance: A multigroup analysis comparing China, Mexico, and Spain

Abstract: This article analyzes firm entrepreneurial orientation across different contexts. Applying institutional theory to entrepreneurship proves the different role of the entrepreneurial orientation dimensions depending on the context. The sample for this study is composed of both small and medium-sized firms from three countries: China, Mexico, and Spain. In the means of testing our hypothesis and thus quantifying the moderating effect of context, a structural equation model PLS-SEM technique and, specifically, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(86 citation statements)
references
References 92 publications
4
75
1
6
Order By: Relevance
“…After Miller (1983) explored entrepreneurship's correlations, further studies have explored the entrepreneurial process. The scholars focused on entrepreneurial behavior and how companies form the basis of entrepreneurial actions and strategic decisions to accomplish high performance ( Basco et al., 2020 ; Li et al., 2009 ; Lumpkin and Dess, 1996 ; Miller and Le Breton–Miller, 2011 ; Wales et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…After Miller (1983) explored entrepreneurship's correlations, further studies have explored the entrepreneurial process. The scholars focused on entrepreneurial behavior and how companies form the basis of entrepreneurial actions and strategic decisions to accomplish high performance ( Basco et al., 2020 ; Li et al., 2009 ; Lumpkin and Dess, 1996 ; Miller and Le Breton–Miller, 2011 ; Wales et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Entrepreneurial orientation has been known to have a positive association with firm performance [8,9]. It has been tested in different contexts and countries [27]. This statement is also argued to be true for technological companies [28].…”
Section: Hypothesis Developmentmentioning
confidence: 97%
“…Growing evidence shows that EO is essential to the sustainability and creation of enterprises and nations' economic stability [28][29][30]. EO encapsulates the processes, provisions, procedures, and decision-making styles used by management to behave in an entrepreneurial manner [31][32][33][34][35][36][37]. Previous research into entrepreneurship identified entrepreneurship as a multidimensional theory of innovation, proactiveness, and risktaking [38].…”
Section: Entrepreneurial Orientationmentioning
confidence: 99%